Creating Ethnocultural Space in the Process of School Education in the Arctic Region - Nikolaeva, Alla Dmitrievna; Marfusalova, Venera Petrovna; Bugaeva, Aya Petrovna; Shadrina, Sofia Nikolaevna (Journal of History Culture and Art Research, 2020)
The article discusses the problem of the development of small schools located in the circumpolar territory of the Russian Federation. The importance of education as a factor in the stable and sustainable development of the indigenous peoples of the Arctic region and in general the formation of human capital in this region is revealed. The aim of the article is to create conditions for increasing the ethnocultural education of the indigenous peoples of the Arctic region. Theoretical and empirical research methods are applied: analysis, systematization, generalization based on an interdisciplinary approach in philosophy, pedagogy, cultural studies, regional studies in education; questioning, diagnosis, experimental work on pedagogical modeling. The result of the study is a systematic study of the cultural foundations in education. A holistic model of ethnocultural educational space for general educational institutions of the Arctic region has been created and implemented. The results of the study can be useful for the development of regional educational programs, educational and methodical literature by university teachers, as well as the introduction of ethnocultural experience in educational institutions of the Arctic region.